2009
DOI: 10.1136/gut.2009.181982
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and lymphoproliferative disorders: the dust is starting to settle

Abstract: The risk of lymphoproliferative disorders (LDs) has become a major concern for clinicians managing patients with inflammatory bowel disease (IBD). Yet it is difficult to distinguish the possible responsibility of immunosuppressive therapy from the background risk due to the inflammatory disorder itself. LDs are clonal B or T cell proliferation showing considerable heterogeneity and the incidence has increased since the 1970s. The strongest and best-established risk factors for LDs are primary and acquired immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 131 publications
1
38
0
Order By: Relevance
“…Within a period of a decade aft er transplantation ~35% of heart transplant recipients will develop a skin with current users. Th e increased risk of NMSC in IBD patients who receive thiopurines was increased with a HR of 5.9 (95% CI, 2.1-16.4; P =0.0006) for ongoing treatment and 3.9 (95% CI, 1.3-12.1; P =0.02) for past exposure in the CESAME cohort study ( 147 ). When assessing the risk based on patient's age; these values were 2.59/1,000 and 1.96/1,000 patient-years for the age group of 50-65 years and 4.04/1,000 and 5.70/1,000 patient-years for patients older than 65 years.…”
Section: Epidemiology In Ibd Patientsmentioning
confidence: 97%
“…Within a period of a decade aft er transplantation ~35% of heart transplant recipients will develop a skin with current users. Th e increased risk of NMSC in IBD patients who receive thiopurines was increased with a HR of 5.9 (95% CI, 2.1-16.4; P =0.0006) for ongoing treatment and 3.9 (95% CI, 1.3-12.1; P =0.02) for past exposure in the CESAME cohort study ( 147 ). When assessing the risk based on patient's age; these values were 2.59/1,000 and 1.96/1,000 patient-years for the age group of 50-65 years and 4.04/1,000 and 5.70/1,000 patient-years for patients older than 65 years.…”
Section: Epidemiology In Ibd Patientsmentioning
confidence: 97%
“…In a study by the investigators at Mayo Clinic, more than 500 patients with Crohn's disease were treated with infliximab, only two patients developed lymphoproliferative disease, and most patients (86%) were also receiving thiopurines (75%) and methotrexate (11%) [44,45]. In another study, PeyrinBiroulet et al performed a meta-ana lysis of 21 placebo-controlled trials designed to evaluate TNF-a inhibitors for Crohn's disease, they found no difference in frequency of malignancies between the TNF-a inhibitor-treated groups and the controls [46].…”
Section: Tnf-a Inhibitors and Hstclmentioning
confidence: 99%
“…It can be postulated that the dysregulation of these immune systems seen in the chronic inflammation associated with IBD may lead to antigendriven lymphocyte proliferation and a relatively unhindered risk of genetic and chromosomal deviations (Sokol and Beaugerie, 2009). Another possibility is that the combination of metabolites, cytokines and chemokines seen in the mucosa of IBD patients promotes mutagenesis in bystander cells.…”
Section: Pathogenesis Of Lymphoma In Ibdmentioning
confidence: 99%
“…Continuing thiopurines but discontinued or never anti-TNFs 13 6.53 3.48 to 11.2 Table 4. SIRs in patients treated with thiopurines and anti-TNF drugs (Beaugerie et al 2009) …”
Section: Risk Of Lymphoma In Patients Treated With Anti-tnf Drugsmentioning
confidence: 99%
See 1 more Smart Citation